A Message to British Pitmen, 1940 (United Kingdom, 1940)
1940 1939-1945 "A Message to British Pitmen, 1940" [HFR0058], 1940 This leaflet from Will Lawther, President of the Mineworkers Federation of Great Britain, urges coal miners to greater productivity to defeat Fascism. The photograph shows Lawther speaking at the Durham Miners Gala.